1981
DOI: 10.1007/bf01002714
|View full text |Cite
|
Sign up to set email alerts
|

Golgi orientation and cell behaviour in the developing pattern of chondrogenic condensations in chick limb-bud mesenchyme

Abstract: Using a silver-impregnation method, the occurrence and significance of Golgi apparatus orientation has been studied in cells contributing to the cartilage condensations in the developing skeleton of the chick limb bud, both in normal embryos and in the talpid mutant, in which the pattern of condensation in situ, and cell behaviour in vitro, is abnormal. Analysis of photographed sections made up as photomontages with a final magnification of X 1000, indicates a sequence of changing Golgi orientation in the cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Golgi orientation in the developing limb bud mesenchyme has previously been explored with respect to the ectoderm [45] and the developing mesenchymal condensations [46],[47]. Interestingly, whereas a slight bias towards the ectoderm was previously reported at later stages of limb development (>E12.5 in the mouse or HH24 in chick), we already see a clear bias at HH21 (Figure 8A,B).…”
Section: Resultssupporting
confidence: 49%
“…Golgi orientation in the developing limb bud mesenchyme has previously been explored with respect to the ectoderm [45] and the developing mesenchymal condensations [46],[47]. Interestingly, whereas a slight bias towards the ectoderm was previously reported at later stages of limb development (>E12.5 in the mouse or HH24 in chick), we already see a clear bias at HH21 (Figure 8A,B).…”
Section: Resultssupporting
confidence: 49%
“…Golgi position relative to the nucleus, a measure of cell polarity, was biased toward the nearest ectoderm as assessed by immunostaining. Earlier studies identified a comparable, though modest, bias during the later stages of mesenchymal outgrowth and condensation Trelstad, 1977, 1980;Ede and Wilby, 1981). Previous investigations also revealed the presence of numerous mesenchymal filopodia from freezefracture and scanning electron microscopy analysis (Ede et al, 1974;Kelley and Fallon, 1983).…”
Section: Limb Bud Elongationmentioning
confidence: 84%
“…At both the light and ultrastructural level, the observed increase in cell density and apparent increase in cell contact in the core areas of the limb suggests cell movement into the area. Mesenchymal cell motility has been argued as a property of limb mesenchyme and as a basis for condensation formation (Bell and Ede, 1978;Ede and Agerbak, 1968;Ede and Wilby, 1981;Gould et al, 1972;Searls, 1967;Thorogood and Hinchliffe, 1975). The failure of cells to move away from a region during growth likewise may contribute as a mechanism to aggregation phenomena (Gould et al, 1972(Gould et al, , 1974.…”
Section: Condensationmentioning
confidence: 98%
“…Changing Golgi orientation in the peripheral nonchondrogenic mesenchymal cells (Holmes and Trelstad, 1977) and in the condensing mesenchymal cells (Ede and Wilby, 1981) accompanies the spatial reorganization of the mesenchyme. A concentric arrangement of cells is centered upon the core cells of the condensing field, these core cells being the first to produce a cartilaginous matrix.…”
Section: Condensationmentioning
confidence: 99%
See 1 more Smart Citation